Socio-cultural Perspective of Senior Citizens Health Status in Nepal - Sharma, Mahendra Prasad (Curriculum Development Journal, 2021)
This study examines the elderly people’s health status differentials according to selected background variables on the basis of Ageing Survey 2014. The general objective of the study is to identify the health status of elderly people in socio-cultural perspective. This study examined the associations of different twelve socio-cultural factors with combination of health outcome (Good or Bad) in older age by applying the cross tables, Chi squire test and binary logistic regression analysis. These variables are selected on the basis of theoretical and empirical studies sighted in the literature reviews. This research is find out only three major socio-cultural factors that make variation determine in the health status of elderly people in Nepal. General literacy status does not impact the elderly health situation in Nepal so high level education need to elderly to improve health status of elderly. Highly appreciating and follow up elderly advices help to increase health status of elderly so it should be utilized in most societies of Nepal. Only Kirat religion elderly are found to be in good health condition than Hindu religion. So other religions of Nepal have not significant impact on health status of elderly compare to Hindu religion.